Intelligent monitoring and evaluation for the prefabricated construction schedule. (28th March 2022) - Yan, Xuzhong; Zhang, Hong; Zhang, Wenyu
Abstract: The prefabricated building construction (PBC) project is sensitive to uncertainties due to the highly required coordination and interdependency among the installation activities, which may cause progress delay. Hence, it is necessary to monitor the installation progress and evaluate the schedule in terms of the project duration to take proactive control actions to avoid actual project delay. This study focuses on intelligent monitoring and evaluation for the PBC schedule by combining the computer vision‐based (CVB) technology, a weighted kernel density estimation (WKDE) method, and the earned duration management (EDM) method. Intelligent and real‐time far‐field detection of the prefabricated components (PCs) and workers is achieved through the CVB technology, which is, respectively, used to measure the progress status of the PC installation works and other manual works by means of the WKDE method. The PBC project duration is then predicted based on the monitored progress status to evaluate the schedule through the EDM method. The proposed intelligent schedule monitoring and evaluation method have been illustrated and justified through a field application. This study contributes to achieving intelligent schedule monitoring and evaluation for the PBC project.